A201 GASTRIC VARICEAL BLEED AS A FIRST PRESENTATION OF AUTOIMMUNE HEPATITIS. (15th March 2019) - AL-Bahlani, A M; Wong, P; Ahmed, N
Abstract: Background: Background: Autoimmune hepatitis (AIH) is a progressive liver disease characterized by hepatic inflammation, positive autoantibodies, and increased levels of immunoglobulin G. It has a broad clinical spectrum ranging from asymptomatic transaminitis to fulminant liver failure. In this case report we highlight upper gastrointestinal bleeding secondary to gastric varices as the first presentation in a child with AIH. Case Report: A 12-year-old previously healthy girl presented to the ER with hematemesis associated with epigastric pain and nausea. She was noted to have mild jaundice a few weeks prior. She had no history of fever, melena or hematochezia. On presentation to the ER, she was tachycardic and hypotensive. She had splenomegaly but no other stigmata of chronic liver disease.She was stabilized with blood transfusion, as well as IV pantoprazole and octreotide and admitted to the PICU. Initial laboratory results were suggestive of liver failure with a Hb 73g/L, platelets 91x10 9 /L, ALT 136 U/L, AST 213 U/L, GGT 51 U/L, direct/total bilirubin 96/37umol/l, albumin 15g/L, and INR 2.42. Abdominal ultrasound showed features suggestive of hepatic fibrosis and portal hypertension. Gastroscopy showed a normal esophagus and portal hypertensive gastropathy with a GOV2 varix with bleeding stigmata which was successfully glued with histocryl. Investigations for chronic liver disease including viral hepatitis, and alpha 1 antitrypsin deficiency were negative. She had a positive ANA and low ceruloplasmin with a normal ophthalmologic exam. The liver biopsy showed chronic hepatitis with moderate activity and stage 4/4 fibrosis. Minimal stainable copper was seen on Orcein stain. EM showed dilatation of mitochondrial cristae and matrix densities. The biopsy thus had features suggestive of Wilson's disease but could not exclude autoimmune hepatitis. She was therefore started on both zinc gluconate and methylprednisolone as treatment for Wilson's disease and autoimmune hepatitis respectively on her 4 th day of hospitalization. Subsequent results revealed a positive anti–liver-kidney microsomal antibody. The repeated serum ceruloplasmin was normal and subsequently the 24 hour urine copper was normal. Genetic testing for Wilson's disease was negative. There was a clinical and biochemical response to treatment with a decrease in her bilirubin (bili-direct 4.5), INR stabilized at 1.8 and her ALT decreased initially but then started to increase gradually reaching 120 U/L. Combination therapy with azathioprine was initiated and zinc was stopped. The endoscopy was repeated 6 weeks and 14 weeks after her initial procedure and theGOV2 varix required histocryl injection on both occasions. Her response to treatment continues to be monitored closely conjointly with the transplant centre to decide on listing for liver transplantation. Aims: See above Methods: Results: Conclusions: Funding Agencies: None